A Rare Cause of Intestinal Obstruction - Mahmood, Mansoor; Akhtar, Nadeem; Ismail, Saqib; Mehmood, Dinar; Zahir, Israr (International Journal of Pathology, 2018)
Angio neuronal dysplasia is relatively rare condition of stomach and intestine which is combination oftwo conditions angio and neuronal dysplastic changes followed by abdominal pain and intestinal obstruction.The current case presented sub acute abdominal obstruction. We present a case of angio- neuronal dysplasia ofterminal ileum and cecum with an unusual mechanism of intestinal obstruction.